Influence of load and position of center of mass on COF in cross-country skiing - Sandberg, J.; Hindér, G.; Holmberg, H.-C.; Almqvist, A.; Larsson, R. (Tribology Letters, 2025)
Cross-country skiers employ various techniques, where the ski is exposed to different forces during the motion. This study utilized a novel sled tribometer to investigate the combined effects of load and positioning of the skier on the coefficient of friction (COF) between the skis and snow. Three different loads (40 kg, 80 kg and 120 kg) were applied to the sled, and the center of mass was systematically varied between three positions behind the binding position: 70mm (leaning forward), 140mm (centered) and 210mm (backward). A variety of skis were used, including different models of skate skis and one classic-style ski with grip wax. The results consistently demonstrated that increasing the load on the sled reduced the COF by up to 15% (from the lowest to highest load), regardless of the position of the center of mass. The position of the center of mass had a minimal effect on COF in most tests. An exception was observed when using grip wax, where a forward-leaning position combined with a heavy load significantly increased the COF (~ 8%) compared to what is expected without grip wax. This load-dependent reduction in the COF was observed across different skis and test sessions. The ski camber profile was measured for all skis in all configurations. In general, increasing the load increases the glide zone length but at the same time increasing the average pressure. The position of the center of mass has little to no effect on the rear glide zone but slightly alters the length and position of the front glide zone. While the mechanisms of friction are discussed, a complete understanding of these mechanisms has not yet been reached.